Specification for carbon and low-alloy steel rods for oxyfuel gas welding (American Welding Society ; Reproduced by World Engineering Xchange (WEX) with the permission of AWS under royalty agreement, 2007)
"This specification prescribes the requirements for classification of carbon and low-alloy steel rods for oxyfuel gas welding. The classification requirements include the mechanical properties of the weld metal. Additional requirements are included for chemical composition of the rod and for manufacture, sizes, lengths, and packaging. A guide is appended to the specification as a source of information concerning the classification system employed and the intended use of the rods. This specification makes use of both U.S. Customary Units and the International System of Units (SI). Since these are not equivalent, each system must be used independently of the other."